2013
DOI: 10.1186/1743-422x-10-293
|View full text |Cite
|
Sign up to set email alerts
|

Combination of autophagy inducer rapamycin and oncolytic adenovirus improves antitumor effect in cancer cells

Abstract: BackgroundCombination of oncolytic adenoviruses (Ads) and chemotherapy drugs has shown promising therapeutic results and is considered as a potential approach for cancer therapy. We previously have shown that autophagy may generate decomposed cellular molecules that can be used as nutrition to support virus replication in cancer cells. In this study, we evaluated a unique combination of the novel oncolytic Ad-cycE with rapamycin, an autophagy inducer and first-line chemotherapeutic drug.MethodsThe combination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 76 publications
0
47
1
Order By: Relevance
“…Interestingly, RIDa was shown to rescue the cholesterol storage phenotype of Niemann-Pick disease type C mutant fibroblasts, and is involved in lipid droplet formation (Cianciola and Carlin, 2009;Cianciola et al, 2013). One can envisage that a combination of autophagy-inducing compounds together with HAdV may enhance oncolytic efficacy of viral therapies (Rodriguez-Rocha et al, 2011;Cheng et al, 2013).…”
Section: Autophagy: Proviral or Antiviral?mentioning
confidence: 99%
“…Interestingly, RIDa was shown to rescue the cholesterol storage phenotype of Niemann-Pick disease type C mutant fibroblasts, and is involved in lipid droplet formation (Cianciola and Carlin, 2009;Cianciola et al, 2013). One can envisage that a combination of autophagy-inducing compounds together with HAdV may enhance oncolytic efficacy of viral therapies (Rodriguez-Rocha et al, 2011;Cheng et al, 2013).…”
Section: Autophagy: Proviral or Antiviral?mentioning
confidence: 99%
“…In addition, the combination of an adenovirus with an autophagy inducer correlates positively with virus replication, improving the efficacy of Ad-mediated oncolysis. Therefore, we explored whether the oncolytic adenovirus loaded to L-carnosine, a mimic of rapamycin, improves antitumor effects in cancer cells (16). LC3II conversion performed in HCT-116 and in A549 cells demonstrates that the complex increases autophagy promoting virus replication only in colon cancer cells (HCT-116).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that virus-induced autophagy correlates positively with virus replication and that the combination of an adenovirus with an autophagy inducer improves antitumor effects in cancer cells (16). L-carnosine has been defined as a mimic of rapamycin, an inhibitor of the mTOR, and so may be able to induce autophagy (17).…”
Section: Oncolytic Adenovirus Loaded With L-carnosine Induces Autophamentioning
confidence: 99%
“…Adhz60 is an E1b-deleted vector similar to dl1520 and H101 and was used as a cancer selective control in these studies [43]. AdGFP is E1 (E1a and E1b) deleted, with green fluorescent protein (GFP) expression driven by the cytomegalovirus (CMV) promoter [35]. AdGFP, as a negative control, does not replicate nor induce cytopathic effects (CPE) [9,23].…”
Section: Adenoviral Vectorsmentioning
confidence: 99%